Rekonstruksi Integrasi Agama dan Sains dalam Perspektif Syed Muhammad Naquib al-Attas serta Relevansinya bagi Pengembangan Pendidikan Agama Islam di Era Modern - Jamil, Sukron; Dewi, Eva; Amir Toedien, Faisal (Zawiyah: Jurnal Pemikiran Islam, 2025)
This article aims to analyze Syed Muhammad Naquib al-Attas's thoughts on the integration of religion and science and its relevance to the development of Islamic Religious Education (PAI) in the modern era. This study uses a qualitative method with a literature review approach, with primary sources in the form of al-Attas' works, such as Islam and Secularism and Prolegomena to the Metaphysics of Islam, as well as secondary sources in the form of related journal articles and books. The results of the study show that al-Attas emphasizes three main concepts in the integration of science, namely the Islamization of science, the Islamic worldview as an epistemological foundation, and the importance of adab and ta’dib in education. Further discussion reveals that al-Attas's thoughts are able to offer a critical Islamic epistemological reconstruction of secularism and scientism, while providing a new direction for the PAI curriculum and learning strategies. The conclusion of the study affirms that al-Attas' paradigm is relevant for building holistic Islamic education, integrating the intellectual, moral, and spiritual aspects of students, and opening opportunities for further research in the field of curriculum and integrative learning practices